Tag-Protector: An Effective and Dynamic Detection of Illegal Memory Accesses through Compile Time Code Instrumentation. (19th June 2016) - Saeed, Ahmed; Ahmadinia, Ali; Just, Mike
Abstract : Programming languages permitting immediate memory accesses through pointers often result in applications having memory-related errors, which may lead to unpredictable failures and security vulnerabilities. A lightweight solution is presented in this paper to tackle such illegal memory accesses dynamically in C/C++ based applications. We propose a new and effective method of instrumenting an application's source code at compile time in order to detect illegal spatial and temporal memory accesses. It is based on creating tags to be coupled with each memory allocation and then placing additional tag checking instructions for each access made to the memory. The proposed solution is evaluated by instrumenting applications from the BugBench benchmark suite and publicly available benchmark software, run-time intrusion prevention evaluator (RIPE), detecting all the bugs successfully. The performance and memory overheads are further analyzed by instrumenting and executing real-world applications from various renowned benchmark suites. In addition, the proposed solution is also tested to analyze the performance overhead for multithreaded applications in multicore environments. Overall our technique can detect a wide range of memory bugs and attacks with reduced performance overhead and higher detection rate as compared to the similar existing countermeasures when tested under the same experimental setup.